CONSIDER THE DEMENTOR: DISCIPLINE, PUNISHMENT, AND MAGICAL CITIZENSHIP IN HARRY POTTER - Bealer, Tracy (Dialogue, 6(3), 2019)
In his 2004 essay “Consider the Lobster”, David Foster Wallace investigated the ethics of boiling alive an aesthetically unappealing, yet sentient and perceiving, creature to augment the pleasure of a human consumer. In the Potterverse, dementors are described by our human heroes as “terrible things” with “rotting” bodies, “unseen” mouths, and characterized as “among the foulest creatures that walk this earth” . Their occupation as guards of Azkaban Prison does little to improve their reputation among wizard-kind. However, how much of the dementors’ evil is ontological? Is it possible that these beings have been actively constructed as villains by wizarding institutions in order to provide a non-human bogeyman for disciplinary purposes? Lurking beneath and at the edges of the books’ representation of dementors are clues about their chosen habitats and habits that suggest wizards have manipulated their existence in order to weaponize them. Dementors operate in the wizarding world not only to literally confine certain bodies in prison, but also to serve as a hated and feared “other” against which wizards can define themselves. Dementors are enlisted as prison guards and assigned the task of punishing wizard lawbreakers because their physical and emotional effects on these magical humans literalize the social punishment of lawbreaking in the wizarding world: social expulsion and death. Via a close reading the reviled dementor, this analysis hopes to open up a wider discussion on wizarding disciplinary techniques, and explore how other hierarchies in the Potterverse are established and maintained. Keywords: J. K. Rowling, Harry Potter series, treatment of dementors, justice system in Harry Potter, rationality in Harry Potter
Keywords: Type of access: Open Access